PLGA–collagen–BPNS Bifunctional composite mesh for photothermal therapy of melanoma and skin tissue engineering. Issue 2 (22nd December 2021) - Sutrisno, Linawati; Chen, Huajian; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract : A PLGA–collagen–BPNS composite mesh was prepared by hybridizing a PLGA knitted mesh with a BPNS-loaded collagen sponge for the photothermal ablation of cancer cells and the promotion of skin regeneration. Abstract : The treatment of melanoma requires not only the elimination of skin cancer cells but also skin regeneration to heal defects. To achieve this goal, a bifunctional composite scaffold of poly(dl -lactic- co -glycolic acid) (PLGA), collagen and black phosphorus nanosheets (BPNSs) was prepared by hybridizing a BPNS-embedded collagen sponge with a PLGA knitted mesh. The composite mesh increased the temperature under near-infrared laser irradiation. The incorporation of BPNSs provided the PLGA–collagen–BPNS composite mesh with excellent photothermal properties for the photothermal ablation of melanoma cells both in vitro and in vivo . The PLGA–collagen–BPNS composite mesh had high mechanical strength for easy handling. The PLGA–collagen–BPNS composite mesh facilitated the proliferation of fibroblasts, promoted the expression of angiogenesis-related genes and the genes of components of the extracellular matrix for skin tissue regeneration. The high mechanical strength, photothermal ablation capability and skin tissue regeneration effects demonstrate that the bifunctional PLGA–collagen–BPNS composite mesh is a versatile and effective platform for the treatment of melanoma and the regeneration of skin defects.